FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN SCARLETT (Studi Pada Toko Online Scarlett Sumbawa) - Subhan Purwadinata; Rizki Nandasari (Fakultas Ekonomi dan Manajemen, 2021)
This study aims to know the effect of cultural, social, personal and psychological factors toward purchasing Scarlett products at the Scarlett Sumbawa online store. The type of this study was Accidental Sampling. The data used were primary and secondary data. The populations in this study were all customers who buy Scarlett products at the Scarlett Sumbawa online store, in which its number were unknown certainty and the technique used to determined sample was Quota sample technique. The number of sample were 10 times the number of variables, therefore the number of samples were 50. The data collection method used in this study was a questionnaire. The data analysis technique used were validity test, reliability test, classical assumption test, t test, f test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression test, and coefficient of determination test. The results of the study showed that cultural, social, personal, and psychological factors had positive and significant effect toward purchasing decisions of Scarlett beauty products at the Scarlett online store Sumbawa. The percentage effect of cultural, social, personal, and psychological factors was 85%. It means that if the cultural, social, personal, and psychological factors increase, the purchasing decisions of Scarlett beauty products at the Scarlett Sumbawa Online Store will increase.